ABCB1 gene polymorphisms and response to chemotherapy in breast cancer patients: A meta-analysis. (December 2017) - Madrid-Paredes, Adela; Cañadas-Garre, Marisa; Sánchez-Pozo, Antonio; Expósito-Ruiz, Manuela; Calleja-Hernández, Miguel Ángel
Abstract: The ABCB1 gene encodes the P -glycoprotein, an efflux pump for some antineoplastic agents which acts as a resistance mechanism to chemotherapy. Three SNPs (C3435T, C1236T and G2677T/A), are the most widely studied in ABCB1. The inconsistent conclusions about the association of these polymorphisms and the response to chemotherapy in breast cancer (BC) patients prompted us to conduct a meta-analysis. A total of nine (770 patients), five (566 patients) and three studies (367 patients) relating the ABCB1 C3435T, C1236T and G2677T/A polymorphisms respectively, were included. The main analysis revealed a lack of association between ABCB1 polymorphisms and response to chemotherapy in every genetic model: C3435T (dominant OR: 0.888; 95%CI: 0.558–1.413), C1236T (dominant OR: 1.968; 95%CI: 0.609–6.362) and G2677T/A (GG vs GT + GA + TT + TA + AA OR: 0.854; 95%CI: 0.418–1.744). Stratification by ethnicity, cancer type and response criteria did not change the pattern of results. The available evidence indicates that three polymorphisms within ABCB1; C3435T, C1236T and G2677T/A, cannot be considered a reliable predictor of response to chemotherapy in BC patients.